La importancia de las funciones de la polícia judicial en el manejo de la cadena de custodia en el sistema penal acusatorio en Colombia (2017)
This article aims to show the importance of the role of the Judicial Police in the management of the chain of custody, since from this point is part of the acceptance of the proof seeking that it has been taken within the established by the Prosecutor's Manual in relation to the material element of evidence and physical evidence, that the proof to be controverted does not claim that there was an adequate management and therefore be lost, since this would leave the judge and the prosecutor without arguments of recovery of the same